Temporary Venoarterial Extracorporeal Membrane Oxygenation: Ten-Year Experience at a Cardiac Transplant Center. (May 2018) - Tran, Bao G.; De La Cruz, Kim; Grant, Stuart; Meltzer, Joseph; Benharash, Peyman; Dave, Ravi; Ardehali, Abbas; Shemin, Richard; Depasquale, Eugene; Nsair, Ali
Objective: Advances in extracorporeal membrane oxygenation (ECMO) have enabled rapid deployment in a wide range of clinical settings. We report our experience with venoarterial (VA) ECMO in adult patients over 10 years and aim to identify predictors of mortality. Design: This is a retrospective analysis of all adult patients undergoing VA ECMO at a tertiary care center from January 1, 2004, to December 31, 2013. Results: A total of 224 consecutive cases were reviewed. Eighty (35.7%) patients survived to discharge and 144 (64.3%) patients died. Patients requiring ECMO for heart transplant graft failure had lower mortality (51.6%) compared to all other etiologies (69.1%; P = .02). Forty-two percent (94 of the 224) of the patients required cardiopulmonary resuscitation (CPR) preceding ECMO and had higher rate of in-hospital mortality (74.5%) compared with patients without cardiac arrest (56.9%; P = .01). Patients with less than 30 minutes of CPR had a mortality rate of 40.0% compared to 91.4% for CPR > 30 minutes ( P = .001). In all, 24.1% of patients (54 of the 224) experienced ECMO-associated complications without significant increase in mortality, and 22.3% (50 of the 224) of the patients were transitioned to ventricular assist devices (VADs) or transplant. Patients bridged to a VAD including left ventricular assist devices and biventricular assist devices had a mortality rate of 56.1% versus 22.2% when bridged directly to transplant ( P = .01). Paradoxically, patients with an ejection fraction (EF) > 35% had a higher mortality compared to patients with an EF < 35% (75.3% vs 49.4%, respectively, P = .001). Conclusion: Extracorporeal membrane oxygenation in patients with heart transplant graft failure had the best outcome. In patients who had cardiac arrest, prolonged CPR > 30 minutes was associated with very high mortality. Paradoxically, patients with EF > 35% had a higher mortality than patients with EF < 35%, likely reflecting patients with diastolic heart failure or noncardiac causes necessitating ECMO. For transplant candidates, direct bridge from ECMO to transplant could achieve a very good outcome.